Pengaruh Kompetensi dan Fasilitas Rumah Sakit terhadap Motivasi Kerja Perawat di RSGM Universitas Prof. Dr. Moestopo (Beragama) - Salma Dhia Firdauzi Putri; Budiharto; Fajarisman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Background : Nurses are the most important human resource in hospitals in terms of carrying out various efforts aimed at optimizing the quality of nurse skills and providing health service to the community. One of the good performance of nurses is influence by the level of enthusiasm or motivation of nurses at work. High motivation can be supported through the competence that nurses have and adequate working condition to make work easier. Objective : Improve the work motivation of nurses by analyzing the influence of competence on the work motivation of nurses, analyzing the hospital facilities on the work motivation of nurses, and analyzing the influence competence and hospital facilities towards work motivation of nurses at RSGM Prof. Dr. Moestopo (Beragama). Materials and Methods : Research is a correlational research using a quantitative approach, descriptive-inferential statistical analysis method, and data analysis technique of correlation and regression in both single and multiple. The sample in this research was dental nurses at RSGM Prof. Dr. Moestopo (Beragama) in total of 50 people. Sample was performed using non-probability sampling method with a purposive sampling technique. Research Result : Indicate that the competence of nurses has an positive and significant influence to the level of work motivation of nurses at RSGM Prof. Dr. Moestopo (Beragama) and hospital facilities have a positive and significant influence on the work motivation of nurses at RSGM Prof. Dr. Moestopo (Beragama) as well. Conclusion : Competence and hospital facilities simultaneously and significantly have an influence on the work motivation of nurses at RSGM Prof. Dr. Moestopo (Beragama).